What are we to make of Gogol’s nationality? - Dibrova, V. (Гоголезнавчі студії, 2009)
The author of the article tries to give the answer on the question «What are we to make of Gogol’s nationality?» exploring Gogol’s language, his rootedness, his world view, his characters and his style. Автор статьи пытается ответииь на вопрос о национальности Гоголя, исследуя его язык, корни, мировоззрение, героев и стиль. Автор статті намагається дати відповідь на питання про національність Гоголя, досліджуючи його мову, коріння, світогляд, героїв і стиль.